CDKAL1 gene variants (rs7756992 and rs10946398) and susceptibility to type 2 diabetes: Evidence from a Jordanian case-control study - Atoum, Manar; Almehsen, Ala' (Acta Biomedica Atenei Parmensis, 2025)
Background: Type 2 diabetes (T2D) is a prevalent metabolic condition characterized by chronic hyperglycaemia due to impaired insulin secretion or sensitivity. The CDKAL1 gene is associated with T2D risk because of its role in insulin biosynthesis, with SNPs such as rs7756992 and rs10946398 exhibiting variable associations across different populations. Objective: This study aims to assess the relationship between CDKAL1 variants rs7756992 and rs10946398 and the risk of T2D in the Jordanian population. Method: We conducted a case-control study involving 200 participants (100 with T2D and 100 matched controls) from Prince Hamza Hospital. Genomic DNA was extracted and analyzed for rs7756992 and rs10946398 using real-time PCR (Allelic Discrimination Assay). Clinical and genetic data were evaluated using SPSS and SNPStats software. Results: No significant association was found between rs7756992 and T2D or any clinical parameters. In contrast, significant differences in total cholesterol (TC) levels were identified between genotypes of rs10946398 within the T2D group (p=0.035) and in LDL cholesterol (LDL-C) levels within the control group (p=0.044). However, no significant association was observed between rs10946398 and T2D risk across all genetic models. Conclusion: The study revealed a significant association between the CDKAL1 rs10946398 variant and TC levels in T2D patients, indicating a potential gene-environment interaction. No overall significant associations with T2D risk were observed for either SNP. Further research with larger sample sizes is required to validate these findings in the Jordanian population.